Childhood stressors in the development of fatigue syndromes: a review of the past 20 years of research. Issue 9 (July 2014) - Borsini, A.; Hepgul, N.; Mondelli, V.; Chalder, T.; Pariante, C. M.
<x content-type="archive" xml:space="preserve">Abstract</x> Background Chronic fatigue syndrome (CFS) and fibromyalgia (FM) are both highly prevalent conditions associated with extreme disability and with the development of co-morbid psychiatric disorders, such as depression and anxiety. Childhood stressors have been shown to induce persistent changes in the function of biological systems potentially relevant to the pathogenesis of both CFS and FM, such as the inflammatory system and the hypothalamic–pituitary–adrenal (HPA) axis. In this review, we examined whether multiple forms of childhood stressors are contributing factors to the development of these disorders, and of the associated psychiatric symptoms. Method Using PubMed, we identified 31 papers relevant to this narrative review. We included cohort studies and case-control studies, without any exclusion in terms of age and gender. No study characteristics or publication date restrictions were imposed. Results Most studies across the literature consistently show that there is a strong association between experiences of childhood stressors and the presence of CFS and FM, with rates of CFS/FM being two- to three-fold higher in exposed than in unexposed subjects. We also found evidence for an increased risk for the development of additional symptoms, such as depression, anxiety and pain, in individuals with CFS and FM with a previous history of childhood stressors, compared with individuals with CFS/FM and no such history. Conclusions Our review confirms that exposure to childhood stressors is associated with the subsequent development of fatigue syndromes such as CFS and FM, and related symptoms. Further studies are needed to identify the mechanisms underlying these associations.